2010
DOI: 10.1684/epd.2010.0294
|View full text |Cite
|
Sign up to set email alerts
|

Reversible sleep‐related stridor during vagus nerve stimulation

Abstract: A 23-year-old woman without history of antecedent vocal, respiratory, or sleep disorders received vagus nerve stimulation (VNS) therapy for refractory partial epilepsy and developed sleep-related stridor during the course of parameter titration. Reduction of VNS current during polysomnography completely eliminated stridor. We conclude that VNS may cause sleep-related stridor in rare cases, expanding the spectrum of known sleep-disordered breathing disorders associated with VNS therapy. Parameter adjustment dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…The study by Malow et al [7] found that the score on the Epworth scale improved from 7.2 AE 4.4 to 5.6 AE 4.5, unrelated to a decrease in ictal frequency or changes in the sleep stages through polysomnographic evaluation. These findings contrast with the case report of St Louis et al [8] in which a patient developed snoring and an increase in the score on the Epworth scale following implantation of the VNS, both of which improved after reducing its pacing times.…”
Section: Vagus Nerve Stimulationcontrasting
confidence: 99%
See 3 more Smart Citations
“…The study by Malow et al [7] found that the score on the Epworth scale improved from 7.2 AE 4.4 to 5.6 AE 4.5, unrelated to a decrease in ictal frequency or changes in the sleep stages through polysomnographic evaluation. These findings contrast with the case report of St Louis et al [8] in which a patient developed snoring and an increase in the score on the Epworth scale following implantation of the VNS, both of which improved after reducing its pacing times.…”
Section: Vagus Nerve Stimulationcontrasting
confidence: 99%
“…This association is consistent with the evidence of vagal inhibition as a means to reduce AHI in patients with severe [21] Observational prospective (III) 10 France 7-18 Refractory epilepsy Polysomnograhy Hsieh [22] Case series, retrospective (III) 9 Canada 6-20 Refractory epilepsy Polysomnograhy Aron [23] Case report (IV) 1 Canada 10 Lennox-Gastaut Polysomnograhy Papacostas [24] Case report (IV) OSAHS, described by Garrigue et al [41]. Apnoeas appear to occur during the ON mode and are dependent on specific stimulation parameters [8,13,14,18,19], meaning its modification can reverse the effects without the need for other interventions in most patients. Perhaps patient comorbidities and risk factors, like age, body mass index or craniofacial anomalies, which are rarely taken into consideration [42], might influence the appearance of apnoea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing frequency to 10 Hz had minimal effects on VNS-induced AHI while the on and off time of the stimulators were the same in all four subjects. Another possibility which was not tested but potentially viable is the stepwise VNS parameter adjustment during positive airway pressure titration, as suggested by another investigator [22]. Perhaps there exists a medium whereby VNS parameters are reduced sufficiently and safely so that PAP may become effective.…”
Section: Discussionmentioning
confidence: 99%